2016
DOI: 10.1037/ppm0000067
|View full text |Cite
|
Sign up to set email alerts
|

Love online: How relationship awareness on Facebook relates to relationship quality among college students.

Abstract: Recent literature has provided evidence that online behaviors may be a manifestation of off-line cognitions; furthermore online self-presentations may shape off-line outcomes. The present study examined the associations between the individual difference variable of authenticity (measured via relationship and dispositional authenticity), relationship awareness on Facebook (conveyed through posting one's relationship status as being "in a relationship," displaying a "partnered" relationship status, posting pictu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…That is, they share more potentially embarrassing relationship information online than they normally do off-line, with this online sharing taking the form of comments or photographs. Because these displays are unusual, they may better represent mate retention tactics than the displays examined by Saslow et al (2013), which are commonplace among satisfied couples (e.g., Emery, Muise, Alpert, & Le, 2015; Steers, Øverup, Brunson, & Acitelli, 2016). Moreover, public relationship displays are only one way Facebook is involved in romantic relationships.…”
Section: Individual Differences In Facebook Relationship Maintenancementioning
confidence: 99%
“…That is, they share more potentially embarrassing relationship information online than they normally do off-line, with this online sharing taking the form of comments or photographs. Because these displays are unusual, they may better represent mate retention tactics than the displays examined by Saslow et al (2013), which are commonplace among satisfied couples (e.g., Emery, Muise, Alpert, & Le, 2015; Steers, Øverup, Brunson, & Acitelli, 2016). Moreover, public relationship displays are only one way Facebook is involved in romantic relationships.…”
Section: Individual Differences In Facebook Relationship Maintenancementioning
confidence: 99%
“…An examination of the current literature confirmed that transient forms of relationship visibility have not received as much attention in research compared to more enduring forms (Cole et al, 2018). Yet, in this study, both enduring and transient forms of actual relationship visibility were examined and, to reduce the common method variance, daily postings were measured by gathering data directly from individuals’ Facebook accounts (Steers et al, 2016).…”
Section: Relationship Visibilitymentioning
confidence: 99%
“…Recent literature has provided evidence that Facebook self-presentations may shape off-line outcomes and that online behaviors may be an expression of off-line cognitions or emotions (Nadkarni & Hofmann, 2012; Saslow et al, 2012; Steers et al, 2016). In the context of intimate relationships, these studies have investigated associations between Facebook self-presentations of coupledom (which is referred to as relationship visibility) and many relational outcomes, such as love, relationship longevity, quality, or commitment (Lane et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Past research has prioritized two major forms of relationship awareness-relationship thinking and talking (Acitelli, 1996(Acitelli, , 2002-which both have positive associations with relationship well-being. For example, studies have shown that when an individual in a romantic relationship frequently thinks and talks about his/her relationship, it makes the partner more content (Acitelli, 1993) and helps to build a quality relationship (Steers, Øverup, Brunson, & Acitelli, 2016;Tan, Overall, & Taylor, 2012).…”
Section: Relationship Awareness On Facebookmentioning
confidence: 99%